시판 포도식초의 이화학 특성, 향기성분, 감각 특성 및 소비자 기호도 조사 - 강민정(Minjeong Kang); 하정헌(Jung-Heun Ha); 신의철(Euicheol Shin); 최해욱(Hae-Wook Choi); 이영승(Youngseung Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구에서는 국내에서 시판되는 포도식초 제품 중 대표 5종(V1, V2, V3, V4, V5)을 선정하여 이화학 특성, 항산화 특성, 향기성분, 감각 특성 및 소비자 기호도에 대해 조사하였다. pH 측정 결과 V2, V3, V5가 유의적으로 높게 나타났으며, 총산도 측정 결과 V5가 유의적으로 가장 높게 나타났다. 휘발성 향기성분 분석 결과 식초의 주된 성분인 초산 계열 물질들은 V1, V3, V4에서 주로 검출되었다. 유기산 함량은 V5에서 가장 높게 나타났다. 소비자의 전반적 기호도는 V4가 유의적으로 높게 나타났으며 PLS 회귀 분석 결과 단맛과 포도향이 소비자 기호도에 긍정적인 영향을, 효모향과 타는 듯한 목넘김이 부정적인 영향을 미치는 것으로 나타났다. 본 연구를 통해 국내 시판 포도식초 5종의 품질 특성에는 큰 차이가 존재하고 소비자 기호도에 긍정적, 부정적 영향을 미치는 인자들이 규명되었다. This study was conducted to investigate the quality characteristics of five different kinds of commercial grape vinegar (V1～V5). Physicochemical characteristics, such as the soluble solid contents, pH, total acidity, color, antioxidant activity, organic acid contents, and volatile compounds were compared among five different kinds of grape vinegar. Moreover, to understand the difference of five different vinegars for their sensory perspective, we also conducted descriptive analysis and consumer testing. The pH was relatively high in V2, V3, and V5, but the total acidity was the highest in V5. The soluble solid contents in V4 were the highest among all the tested products. As a result of volatile flavor analysis, acetic acid, which is the main component of vinegar, was mainly found in V1, V3, and V4. The total organic acid content was the highest in V5. Based on sensory evaluation, V4 showed the highest overall liking. According to the partial least squares regression analysis, sweetness and grape flavor might have a positive influence on consumers’ overall liking. However, yeast flavor and burning sensations may negatively affect consumers’ overall liking. There were marked variations in the quality characteristics and sensory evaluation of the five different commercially available vinegars. Therefore, it is logically postulated that there is a broad range of quality characteristics of commercial vinegars in the current marketplace. KCI Citation Count: 3